Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Pegawai Honorer Sekretariat DPRD Kabupaten Batu Bara - Najwa Hakim; Nidaul Hasanah; Eka Mayastika Sinaga (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2026)
This study aims to determine the effect of compensation and work discipline on the performance of honorary employees at the DPRD Secretariat of Batu Bara Regency. This type of research is quantitative descriptive. The population in this study consisted of 40 honorary employees using a saturated sampling technique. Data collection was carried out through questionnaires. The analytical method used is multiple linear regression with SPSS. The results showed that compensation has a significant effect on employee performance, work discipline has a significant effect on employee performance, and simultaneously compensation and work discipline have a significant effect on the performance of honorary employees at the DPRD Secretariat of Batu Bara Regency.